IMPLEMENTASI E-LEARNING DENGAN METODE ASYNCHRONOUS UNTUK MENINGKATKAN MOTIVASI PEMBELAJARAN DENGAN PENDEKATAN TAM STUDI KASUS PADA SMK INSAN KREATIF - Indarti, Indarti (Jurnal Pilar Nusa Mandiri, 2014)
The development of information technology and is rapidly increasing in this era of globalization, it was probably inevitable again, one of which is the development of Internet technology in all fields, not least in the field of education. SMK INSAN CREATIVE as an educational institution has a problem in transforming the conventional education into digital form, the problem is the lack of time that occurs between teacher and student communication, the difficulty of finding information or material that is taught, and the difficulty of teachers in the delivery of content to students. For learning the E-Learning system, more focused on providing education and training materials as learning evaluation was done. And communication between students and students, teachers and teachers, and students and teachers to be able to interact with one another. As the process of learning to be more interactive with each other. Digital learning activities undertaken include obtaining materials and interactive exercises. The results of the exercise undertaken by the student can be used as a parameter of learning success that has been done. Communication can be done on the E-Learning system, among others, the communication between students and students, teachers with teachers, and teachers with the students. Communication has been hampered by limitations of distance and time can now be addressed. Because of the researcher to build and design the application of web-based E-Learning to enhance the students' learning motivation. Hopefully, by the application of E-Learning, these teachers will be easier to deliver material to be conveyed and for students to better understand the material provided, as a method of learning is given more interactive and fun.